Implementation ofVision PSOFastSLAM Algorithm for Unmanned Aerial Vehicles in Mine Environment - LIU Shu-chi; YANG Wei (Journal of Harbin University of Science and Technology)
In order to realize the autonomous flight of Unmanned Aerial Vehicle (UAV) in the mine environment without GPS and also precise positioning it, an algorithm called Fast Simultaneous Location and Mapping (FastSLAM) which is based on RaoBlackwellized particle filter is proposed.Firstly, an artificial road sign suitable for underground mine was designed and the mathematical model of Simultaneous Location and Mapping (SLAM) algorithm for UAV was established.Then an improved algorithm called PSOFastSLAM was proposed to improve the accuracy, to estimate the pose of UAV and the position of guideposts and to achieve the accurate positioning and map building for UAV.Finally, the simulation experiment is simulated, simulation results show that PSOFastSLAM algorithm can improve the particle degeneration problem in FastSLAM algorithm effectively and improve the positioning accuracy of UAV.